Characteristics of carcasses and meat from feedlot-finished buffalo and Bos indicus (Nellore) bulls - Mello, J. L.M. [UNESP]; Rodrigues, A. B.B. [UNESP]; Giampietro-Ganeco, A. [UNESP]; Ferrari, F. B. [UNESP]; Souza, R. A. [UNESP]; Souza, P. A. [UNESP]; Borba, H. [UNESP] (CSIRO Publishing, 2018)
The trade of buffalo meat is very limited in Brazil, where it is still considered exotic, and ∼90% of it is marketed as cattle meat. The present study compared qualitative characteristics of the longissimus muscle from buffalo and cattle. Eighty uncastrated male bovids (40 Mediterranean × Murrah crossbred buffaloes and 40 Nellore cattle) with an average age of 21 months and initial average bodyweight of 350 kg and 305 kg respectively, were confined for 102 days. Buffalo carcass had lower dressing-out percentage (P < 0.0001 52.1% vs 57.2%) than did cattle carcass buffalo meat had greater fat cover (P < 0.0001 13.8 vs 8.1 mm) and, consequently, lower cooling loss (P < 0.0001 1.3% vs 1.8%) than did cattle meat also had lower cooking loss (P = 0.0120 29.42% vs 31.31%), lower collagen content (P < 0.0001 4.81% vs 5.73%), higher moisture (P = 0.0027 75.13% vs 74.55%), and lower atherogenicity index (P = 0.0008 0.61 vs 0.70) than did cattle meat. There was no difference (P = 0.13) between buffalo and cattle regarding cold carcass weight (251 kg and 244.8 kg respectively). Tenderness, fat, and omega-6: omega-3 fatty acid ratio were also similar in both meats. The buffalo carcass provides higher yield of cuts of high commercial value than does the cattle carcass it has similar or better physical and chemical properties than beef and a lower percentage of polyunsaturated fatty acids, making it less susceptible to rancidity. Cattle meat has higher concentrations of C12:0 and C14:0 fatty acids, which are related to increased serum low-density lipoprotein and cholesterol concentrations, while buffalo meat is a rich source of C18:0 and C18:1n9c fatty acids, which help in the prevention of cardiovascular diseases.
Keywords: Bubalus bubalis; collagen; fatty acids; meat quality; tenderness